Insights into the role of a cardiomyopathy-causing genetic variant in ACTN2 - Broadway-Stringer, S; Jiang, H; Wadmore, K; Hooper, C; Douglas, G; Steeples, V; Azad, A; Singer, E; Rayet, J; Galatik, F; Ehler, E; Bennett, P; et al. (MDPI, 2023)
Pathogenic variants in ACTN2, coding for alpha-actinin 2, are known to be rare causes of Hyper-trophic Cardiomyopathy. However, little is known about the underlying disease mechanisms. Adult heterozygous mice carrying the Actn2 p.Met228Thr variant were phenotyped by echocar-diography. For homozygous mice, viable E15.5 embryonic hearts were analysed by High Reso-lution Episcopic Microscopy and wholemount staining, complemented by unbiased proteomics, qPCR and Western blotting. Heterozygous Actn2 p.Met228Thr mice have no overt phenotype. Only mature males show molecular parameters indicative of cardiomyopathy. By contrast, the variant is embryonically lethal in the homozygous setting and E15.5 hearts show multiple morphological abnormalities. Molecular analyses, including unbiased proteomics, identified quantitative abnormalities in sarcomeric parameters, cell cycle defects and mitochondrial dys-function. The mutant alpha-actinin protein is found to be destabilised, associated with increased activity of the ubiquitin-proteosomal system. This missense variant in alpha-actinin renders the protein less stable. In response, the ubiquitin-proteosomal system is activated; a mechanism which has been implicated in cardiomyopathies previously. In parallel, lack of functional al-pha-actinin is thought to cause energetic defects through mitochondrial dysfunction. This seems, together with cell cycle defects, the likely cause of death of the embryos. The defects also have wide-ranging morphological consequences.